Aplicaciones de la toxina botulínica en glándulas salivales - León B., Francisca; León B., Ricardo; Bravo C., Gustavo (Revista Hospital Clínico Universidad de Chile, 2011)
Botulinum toxin is a neuromodulator produced by Clostridium botulinum, a gram-negative, anaerobic bacterium responsible for botulism. The clinical utility of botulinum toxin initially became evident in the treatment of strabismus. Subsequently, botulinum toxin has been used for a variety of other medical conditions such as muscular hyperactivity, including blepharospasm, hemifacial spasm, and cervical dystonia. In addition to its well-known applications, within the properties of botulinum toxin are those that make possible the treatment of various diseases affecting salivary glands and oral cavity. Recently there has been an important development inresearch and finding new applications in otolaryngology. Recent studies have demonstrated the advantages of botulinum toxin injected into the salivary glands of patients who present drooling, reducing the salivary flow and improving their quality of life. In the same way it has proven to be effective as a treatment of sialocele in patients with parotid gland surgery. In parotid and pharyngocutaneous fistula it has proven effective in reducing the salivary flow, facilitating the closure of the defect. Moreover, in patients with Frey’s syndrome it has been effective reducing symptoms and improving quality of life. It has also been histologicallydemonstrated its protective effect on the glandular damage in patients undergoing radiotherapy.